2015
DOI: 10.1007/s12011-015-0294-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of Serum Heavy Metals and Trace Element Concentrations with Reproductive Hormone Levels and Polycystic Ovary Syndrome in a Chinese Population

Abstract: To investigate the serum concentrations of 11 heavy metals and trace elements in patients with polycystic ovary syndrome (PCOS). A total of 369 women (including 96 patients with PCOS) were studied. No differences with statistical significance in the median barium, cadmium, lead, arsenic, chromium, gallium, strontium, and vanadium concentrations were observed between the patients with PCOS and the control group. Serum nickel (Ni) (P = 0.000) and copper (Cu) (P = 0.000) levels were significantly higher, but zinc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
67
3
4

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(81 citation statements)
references
References 37 publications
7
67
3
4
Order By: Relevance
“…Therefore, zinc deficiency may have a role as either an initiator or promoter of the underlying mechanisms and metabolic features of PCOS by means of causing insulin resistance, decreasing antioxidant capacity and inducing apoptosis. Moreover, it is possible that decreased antioxidant capacity can be aggravated by zinc deficiency and insulin resistance in women with PCOS [27].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, zinc deficiency may have a role as either an initiator or promoter of the underlying mechanisms and metabolic features of PCOS by means of causing insulin resistance, decreasing antioxidant capacity and inducing apoptosis. Moreover, it is possible that decreased antioxidant capacity can be aggravated by zinc deficiency and insulin resistance in women with PCOS [27].…”
Section: Discussionmentioning
confidence: 99%
“…Of those, two were excluded after full text review because they did not focus on the serum levels of trace elements [40,41]. The six articles [42][43][44][45][46][47] that were included in the systematic review presented data on serum or plasma levels of chromium, cobalt, copper, manganese, nickel, selenium, vanadium, and zinc.…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 describes the characteristics of the six studies included in the systematic review. One study focused on a Chinese population [42], another study on women from India [46], and four on Turkish women [43][44][45]47]. All were casecontrol studies and used the 2003 Rotterdam criteria [2] to diagnose PCOS.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…As well our results agree with Line ,et al who explained the elevated lead level observed in some rural areas by the fact that some villages are polluted with high concentration of lead in soil and household dust that subsequently carry lead exposure to the population there causing elevated lead level [18] [19] [20]. Air polluted by oxides and minerals more dangerous on human health where through breathing pollutants move by one hundred percent to human blood and features Baghdad city like all cities abundance cars which use fuel have dangerous toxic which include lead which effects significantly on the patients , elderly and pregnant women posing a risk to fetuses ,High lead level in the blood causes anemia and lakes of hemoglobin in the blood this may lead to liver kidney and brain damage and it was up to the central nervous system [21].…”
Section: Resultsmentioning
confidence: 99%